2017
DOI: 10.3892/mmr.2017.6613
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation-inhibiting pathways in liver regeneration

Abstract: Liver regeneration, an orchestrated process, is the primary compensatory mechanism following liver injury caused by various factors. The process of liver regeneration consists of three stages: Initiation, proliferation and termination. Proliferation‑promoting factors, which stimulate the recovery of mitosis in quiescent hepatocytes, are essential in the initiation and proliferation steps of liver regeneration. Proliferation‑promoting factors act as the 'motor' of liver regeneration, whereas proliferation inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 160 publications
(164 reference statements)
0
35
0
Order By: Relevance
“…It has been proposed that these factors would act as a "brake", controlling the speed of proliferation and the terminal point of the process, and even ensuring the right direction, preventing oncogenesis. An extensive review focused in the termination phase has been recently published (Liu and Chen, 2017). For this reason, this phase is as important as the previous ones, and more studies should be performed to decipher its molecular mechanisms.…”
Section: Termination Phasementioning
confidence: 99%
“…It has been proposed that these factors would act as a "brake", controlling the speed of proliferation and the terminal point of the process, and even ensuring the right direction, preventing oncogenesis. An extensive review focused in the termination phase has been recently published (Liu and Chen, 2017). For this reason, this phase is as important as the previous ones, and more studies should be performed to decipher its molecular mechanisms.…”
Section: Termination Phasementioning
confidence: 99%
“…Then, growth factors and cytokines guide the progression of liver regeneration through expression of several cell-cycle-related proteins mainly by PI3K/AKT, wnt/β-catenin, Ras/MAPK, and JAK/STAT signaling pathways [2]. Equally important are pathways that control the speed of proliferation and determine the terminal point of liver regeneration [3]. Previously, we demonstrated that expression and activation of p21, an inhibitor of a subset of cyclin dependent kinases including cdc2, is a pivotal factor in arrested liver regeneration [4].…”
Section: Introductionmentioning
confidence: 99%
“…P21 is a fundamental cell cycle control checkpoint regulator, in particular, as it is inhibiting the G2-M phase progression. As such, it is downstream of many signaling networks, including those induced by p53, injury, growth factors (TGF-β), and inflammatory cytokines [3].…”
Section: Introductionmentioning
confidence: 99%
“…In liver, TGF‐β as well as other cytokines like TNF‐α, IL‐1, and IL‐6 function as inhibitors of regeneration (reviewed in Liu et al). Likewise, p53 inhibition with antisense oligonucleotides or in p53 −/− mice, leads to increased hepatocyte proliferation, although p53 function in other organs might be different .…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, p53 inhibition with antisense oligonucleotides or in p53 −/− mice, leads to increased hepatocyte proliferation, although p53 function in other organs might be different . Along this line, other oncogenes such as p21, Bcl‐2, and NDRG2 have been shown to inhibit liver regeneration (reviewed in Liu et al).…”
Section: Introductionmentioning
confidence: 99%